The Association Between Pediatric Faculty Factors and Resident Physician Ratings of Teaching Effectiveness - Potisek, Nicholas M. (Glob Pediatr Health, 2019)
Background. Faculty factors not inherently related to teaching effectiveness can influence teaching ratings. No studies have focused on pediatric faculty who possess unique differences from general medical faculty. Methods. We designed a retrospective observational study to compare faculty teaching ratings with measured factors across 3 academic pediatric institutions. Results. Our study included 196 faculty members. The majority (76%) of variation in teaching effectiveness ratings was not accounted for by any measured variable, but 24% was attributed to measurable factors. Increased resident exposure (sequential r(2) = .10, P < .0001) significantly affected teaching effectiveness. Variation between resident ratings of pediatric faculty teaching can be partially explained by measured factors not necessarily related to teaching effectiveness. Conclusions. The identification of faculty factors that significantly contribute to rating variation can enhance interpretation of these rating.